Nickel-catalysed selective migratory hydrothiolation of alkenes and alkynes with thiols - Yulong Zhang (Nature Portfolio, 2019)
Construction of C–S bonds via C–H functionalization is an attractive route to organosulfur compounds. Here, the authors show the synergistic combination of NiH-catalysed alkene isomerization and subsequent thiolation to afford remote hydrothiolation products from alkenes (or alkynes) and thiols under mild conditions.